Mosquito-borne flaviviruses and type I interferon: catch me if you can! - Zoladek, Jim; Nisole, Sébastien (Frontiers in Microbiology, 2023)
Mosquito-borne flaviviruses include many viruses that are important human pathogens, including Yellow fever virus, Dengue virus, Zika virus and West Nile virus. While these viruses have long been confined to tropical regions, they now pose a global public health concern, as the geographical distribution of their mosquito vectors has dramatically expanded. The constant threat of flavivirus emergence and re-emergence underlines the need for a better understanding of the relationships between these viruses and their hosts. In particular, unravelling how these viruses manage to bypass antiviral immune mechanisms could enable the design of countermeasures to limit their impact on human health. The body's first line of defense against viral infections is provided by the interferon (IFN) response. This antiviral defense mechanism takes place in two waves, namely the induction of type I IFNs triggered by viral infection, followed by the IFN signaling pathway, which leads to the synthesis of interferon-stimulated genes (ISGs), whose products inhibit viral replication. In order to spread throughout the body, viruses must race against time to replicate before this IFN-induced antiviral state hinders their dissemination. In this review, we summarize our current knowledge on the multiple strategies developed by mosquito-borne flaviviruses to interfere with innate immune detection and signaling pathways, in order to delay, if not prevent, the establishment of an antiviral response.